2017
DOI: 10.3126/nepjoph.v8i2.16993
|View full text |Cite
|
Sign up to set email alerts
|

Direct microscopy in suppurative keratitis: a report from tertiary level hospital in Nepal

Abstract: Introduction: Infective keratitis is an ocular emergency that requires prompt diagnosis for appropriate management. This study was done todetermine the sensitivity, specificity and predictive values of Gram stain and potassium hydroxide (KOH) wet mount in the diagnosis of suppurative keratitis. Materials and methods: A prospective hospital based study of all patients with clinically diagnosed suppurative keratitis presenting between January 2011 and June 2012 was carried out. Corneal scrapes were taken and sub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 18 publications
1
5
0
Order By: Relevance
“…From other reports, the range of sensitivity of Gram stain had been 50 to 100% and for specificity from 77 to 97.6%. 4,7,21,22 Similarly for KOH, the reported range of sensitivity had been from 54 to 99% and specificity from 94 to 99%. 4,7,21,22 The PPV and NPV for bacteria were greater in our study than those reported by Rai et al 22 but for fungus both values were less compared to the same study ( Table 5).…”
Section: Discussionmentioning
confidence: 98%
“…From other reports, the range of sensitivity of Gram stain had been 50 to 100% and for specificity from 77 to 97.6%. 4,7,21,22 Similarly for KOH, the reported range of sensitivity had been from 54 to 99% and specificity from 94 to 99%. 4,7,21,22 The PPV and NPV for bacteria were greater in our study than those reported by Rai et al 22 but for fungus both values were less compared to the same study ( Table 5).…”
Section: Discussionmentioning
confidence: 98%
“…17,18 The higher number of cases among females, in our study could be because of significant contribution of female population to the agricultural force as compared to males who quite often remain away for outdoor activities in search of employment. 19 Thirty-three (39.3%) of the subjects were farmers by occupation. In Nepal, majority of population is involved in agricultural work and various types of manual labors.…”
Section: Discussionmentioning
confidence: 99%
“…Together, these two medications cover the majority of pathogens that cause infectious keratitis in Nepal. [18][19][20][21][22][23] The FCHV administered the first dose of the antimicrobial ointments. Participants were asked to return to the FCHV for a follow-up examination after 3 days, at which point the FCHV re-examined the affected eye with fluorescein and asked an open-ended question about adverse events.…”
Section: Methodsmentioning
confidence: 99%
“…29 However, Pseudomonas and Fusarium account for a small fraction of corneal ulcers in Nepal, and very few abrasions in the intervention arm did not heal after the 3-day course of study antimicrobials, suggesting that the medications chosen for the trial were sufficient for prophylaxis purposes. [18][19][20][21][22][23] Finally, as the study was performed in a specific area of Nepal, it is not clear whether the results can be generalised to other settings. Given the results of the exploratory analyses, further study in areas that are rural or remote could be worthwhile.…”
Section: Table 3: Subgroup Analysesmentioning
confidence: 99%